Value generation for customers of industrial products. Case study of metal double-layer polypropylene bioriented laminate to package food (2019)
This article presents the qualitative stage of a procedure that aims to determine the Client Perceived Value (CPV) of an industrial product. The result of this study is the definition of the characteristics that final users take into account to select their suppliers. The evaluation was based on the product “metal double-layer polypropylene bioriented laminate to package food”. The applied procedure is an example that could be repeated, mutatis mutandis, for any kind of product or service.